Adaptive resource management in multiple targets tracking for co‐located multiple input multiple output radar. Issue 9 (24th July 2018) - Cheng, Ting; Li, Shuyi; Zhang, Jie
Abstract : Co‐located multiple input multiple output (MIMO) radar is one kind of new style radar, whose transmitting waveforms of each sub‐array are orthogonal to each other. Compared with phased array radar, its beam width is wider. Therefore, different targets may be illuminated simultaneously with one beam in co‐located MIMO radar. An adaptive resource management in tracking for co‐located MIMO radar is proposed, where the sub‐array number, the illuminated targets set and the transmitting waveform of the system can be controlled. The optimal parameters are chosen according to a cost function that takes both the desired tracking precision and consumed energy into consideration. Simulation results demonstrate the effectiveness of the algorithm. Using the algorithm, co‐located MIMO radar can achieve the desired tracking precision with less cost compared with phased array radar.